2004
DOI: 10.5005/jcdp-5-3-66
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Lower Third Molar Conditions on the Re-Crowding of Lower Anterior Teeth in the Absence of Tight Interproximal Contacts One-Year Post Orthodontic Treatment: A Pilot Study

Abstract: The role of lower third molars in lower incisor crowding is a debatable topic. Some believe the presence or eruption of lower third molars is associated with the crowding of mandibular incisors, others negate such association. Thirty-two newly debonded orthodontic patients, with ages ranging from 14-19 years, were randomly selected. No retainers were used for the lower dental arch. Removal of tight interproximal contacts of the lower anterior teeth was created and maintained by periodic abrasive stripping ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The Ganss ratio calculations in their study showed that lower first and second molars and the second premolars are inclined mesially if there was insufficient space for the lower third molars. Buschang and Shulman (2003), 18 Shanley (1962), 19 and AI Balkhi et al (2004) 20 concluded in their respective studies that third molars were not associated with crowding and significant greater crowding took place during adulthood which was in concordance with our study. Zachrisson (2005) 21 also denies a correlation between third molar eruption and anterior incisor crowding.…”
Section: Discussionsupporting
confidence: 91%
“…The Ganss ratio calculations in their study showed that lower first and second molars and the second premolars are inclined mesially if there was insufficient space for the lower third molars. Buschang and Shulman (2003), 18 Shanley (1962), 19 and AI Balkhi et al (2004) 20 concluded in their respective studies that third molars were not associated with crowding and significant greater crowding took place during adulthood which was in concordance with our study. Zachrisson (2005) 21 also denies a correlation between third molar eruption and anterior incisor crowding.…”
Section: Discussionsupporting
confidence: 91%
“…The action of multiple factors at different stages of cranial development may contribute to the lower crowding. The pressure on the back of the dental arch due to physiological mesial slide; the anterior component of occlusal force on mesially inclined teeth, the mesial vector due to muscle contraction, or the presence of the third molar development can cause forward movement of the posterior teeth and therefore shortening the dental arc and increase the crowding (12). The influence of late mandibular development (8) provoking changes in the complex growth pattern can also result in anterior crowding (7), changes in the muscular function of the cheeks, lips and tongue can change the dental balance (9) and mouth breathing also may cause muscular unbalance and provoke lower incisor crowding.…”
Section: Discussionmentioning
confidence: 99%
“…Ganss ratio is the ratio between the third molar width and the retromolar space, meaning that when such space is sufficient the presence of the third molars does not cause tooth crowding; conversely, when such space is reduced the presence of the third molars can cause tooth crowding. Another theory was suggested by Al-Balkhi [ 20 ], who reported that third molars did not cause recrowding of the mandibular anterior teeth when interproximal contacts were removed. The hypothesis is that the mesial force of the erupting molars cannot be transmitted through the teeth in absence of interproximal contacts, thus preventing anterior tooth crowding.…”
Section: Discussionmentioning
confidence: 99%